A highly sensitive and selective method for the determination of ceftiofur sodium in milk and animal-origin food based on molecularly imprinted solid-phase extraction coupled with HPLC-UV. (15th June 2021) - Cheng, Guohao; Zhao, Juan; Wang, Xiaoyue; Yang, Can; Li, Shiying; Lu, Tong; Li, Xiang; Wang, Xuefeng; Zhu, Guifen
Highlights: A MISPE-HPLC-UV method for analysis of ceftiofur sodium was developed. MISPE column was found to have excellent selectivity of ceftiofur sodium by against the commercial column. The proposed system has a lower LOD and LOQ value compared with other methods. The established method can detect ceftiofur sodium in milk and animal-origin food. Abstract: The effective analysis of cephalosporin antibiotics in food animals has attracted considerable attention. Herein, a high-performance liquid chromatograph equipped with a UV method based on molecularly imprinted-solid phase extraction (MISPE-HPLC-UV) was developed for preconcentration, cleanup and determination of ceftiofur sodium (CTFS) in food samples. In this method, an eco-friendly molecularly imprinted polymer (MIP) was synthesized and employed as an adsorbent, which exhibited excellent selectivity towards CTFS in water, and adsorption equilibrium could be reached within 1 h. Under the optimized conditions, good linearity was obtained for CTFS in the range of 0.005–1.0 mg L −1 with a lower LOD of 0.0015 mg L −1, and the average recoveries were higher than 91.9% (RSD less than 8.5%) at three spiked levels in milk, chicken, pork and beef samples. After 20 cycles, the recovery of the MISPE cartridge for CTFS was still higher than 95%, which proved that the MISPE-HPLC-UV method was highly sensitive and selective for the analysis of CTFS in food samples.